FAKTOR-FAKTOR YANG MEMENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - ERIC ERIC; EDRIC KURNIADI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to analyze empiricallythe influence of CEO turnover, company size, debt ratio, return on assets, company losses, current ratio, external auditor, and audit tenure to audit report lag. The sample of this research uses non financial companies listed on the Indonesia stock exchange during 2015-2017. There are 323 companies that match the criteria using purposive sampling method. This study uses multiple regression methods to see the effect of each variable on audit report lag. The results of the study show that CEO turnover, company size, return on asset, loss, and audit tenurehave an influence on audit report lag. Leverage, current ratio and external auditor does not have an influence on audit report lag